The social interaction learning styles of science and social science students - Jaafar Sidek, Hamidah; Muhamad Noor, Sarina; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Students have a variety of styles in the process of learning .One of the model of learning styles is the social aspect on how the students interact with their instructors and peers. This research employs the social interaction learning style theory by Grasha and Riechmann. The objectives of this study are to identify the social interaction learning style in relation to the students’ age, gender, hometown and academic performance. The study also looks at the differences of learning style between different programs (science and social-science) taken by the students. The instrument, Grasha Riechmann Learning Style Survey (GRLSS) was distributed to 531 students. However, only 77% responded. Some of the findings support previous research, while others are inconsistent. Basically, the social interaction learning style adopted by different students in different programs differed in their independent learning style. With this result, instructors can design a better instructional pedagogy based on the students’ learning style.